Mechanism of Ferroptosis and Its Role in Spinal Cord Injury - Li, Fei; Wang, Haifan; Chen, Hao; Guo, Jianing; Dang, Xiaoqian; Ru, Yi; Wang, Haoyu (Frontiers in Neurology, 2022)
Ferroptosis is a non-necrotic form of regulated cell death(RCD) that is primarily characterized by iron-dependent membrane lipid peroxidation and is regulated by cysteine transport, glutathione synthesis, and glutathione peroxidase 4 function as well as other proteins including ferroptosis suppressor protein 1. It has been found that ferroptosis played an important role in many diseases, such as neurodegenerative diseases and ischemia-reperfusion injury. Spinal cord injury(SCI), especially traumatic spinal cord injury, is an urgent problem worldwide due to its high morbidity and mortality, as well as the destruction of functions of the human body. Various RCDs, including ferroptosis, are found in SCI. Different from necrosis, since RCD is a form of cell death regulated by various molecular mechanisms in cells, the study of the role played by RCD in SCI will contribute to a deeper understanding of the pathophysiological process, as well as the treatment and functional recovery. The present review mainly introduces the main mechanism of ferroptosis and its role in SCI, so as to provide a new idea for further exploration.